Regulatory T cell‐derived interleukin‐15 promotes the diversity of immunological memory. Issue 1 (4th November 2022) - Madi, Alaa; Wu, Jingxia; Ma, Sicong; Weisshaar, Nina; Mieg, Alessa; Hering, Marvin; Ming, Yanan; Zettl, Ferdinand; Mohr, Kerstin; ten Bosch, Nora; Schlimbach, Tilo; Hertel, Franziska; et al.
Abstract: While the immunosuppressive function of regulatory T (Treg) cells has been extensively studied, their immune‐supportive roles have been less well investigated. Using a lymphocytic choriomeningitis virus (LCMV) Armstrong infection mouse model, we found that Treg cell‐derived interleukin (IL)‐15 is required for long‐term maintenance of the KLRG1 + IL‐7Rα − CD62L − terminal effector memory CD8 + T (tTEM) cell subset, but dispensable for the suppressive function of Treg cells themselves. In contrast, deletion of Il15 from other sources, including myeloid cells and muscles, did not affect the composition of the memory CD8 + T cell pool. Our findings identify Treg cells as an essential IL‐15 source maintaining tTEM cells and suggest that Treg cells promote the diversity of immunological memory. Abstract : We investigated the identity of IL‐15 producing cells using several mouse strains with cell type‐specific loss of IL‐15 expression. After the resolution of acute infection, IL‐15 secreted by regulatory cells, but not skeletal muscles or myeloid cells, was required for the maintenance of a subset of memory cells referred to as terminal effector memory T cells. These KLRG1 + IL‐7Rα − CD62L − similarly contracted in mice with gremline Il15 deletion. TCM: central memory T cells. TEM: effector memory T cells. tTEM: terminal effector memory T cells.